Education on How to Express and Correct Breast Milk Storage Techniques for Working Mothers - Agustina, Ika; Noviasari, Ita (STIKes Patria Husada Blitar, 2021)
Exclusive breastfeeding for infants up to the age of 6 months reaches 42% while the WHO target wes at least 50%. To increase the coverage of breastfeeding, new mothers who have passed leave and have to return to work can carry out the management of Dairy Mother's Milk (ASIP) (Riskesdas, 2013). According to Kristiyansari (2009) working mothers can still breastfeed, before going to work breastfeed their babies first, then at work mothers pump breast milk and store the milk then when they get home the milk is given to the baby or stored in the refrigerator. After giving the counseling, conducting questions and answers and discussions, many asked about how to pump breast milk and how to store breast milk, especially for working mothers. Furthermore, the evaluation wes given questions to the mother and can answer even though it is not perfect in providing answers, here it appears that there is an understanding that has been received by the mother after counseling. By being given this counseling, it is hoped that from now on, mothers will learn and not be ashamed to add information to health workers about how to express and the correct technique for storing breast milk for working mothers. So that by the time the mother is working, the mother is ready and able to pump breast milk and the mother can store breast milk properly